Exploring the Sobre Vote-buying in Rural Villages: The Lived Experiences of Poor Voters in the Philippines - Graham Naz; Bryan Fruto (Recoletos Multidisciplinary Research Journal)
Empirical evidence showed the prevalence of vote-buying in the country, particularly in rural areas targeting poor voters. This study explores the lived experiences of poor voters from rural areas on sobre vote-buying, the most prevalent type in the province. Semi-structured interviews were conducted by purposively selecting participants who experienced sobre vote-buying. Data gathered were analyzed through thematic analysis. Seven themes were developed to describe the participants' experience with sobre vote-buying. The study concluded that sobre vote-buying follows an established chain, keeps voters’ commitment, and furthers the patriarchal system. It likewise gauges the candidates’ seriousness to win. It is socially accepted due to its prevalence and justified by voter’s perception of rampant government corruption and inefficiency. To some extent, it remains an adequate inducement as participants lament the lack of trustworthy and competent candidates. The study recommends multisectoral voters' education, focusing on the ill effects of electing corrupt and incompetent officials.